Effect of Inflation, Interest Rates, and NIKKEI 225 Index on Composite Stock Price Index in the Capital Markets of 9 ASEAN Countries 2019-2023 - Ismono, Fransiskus Pawang; Suripto, Suripto; Damayanti, Damayanti (PT. Riset Press International, 2025)
This research investigates the influence of inflation, interest rates, and the Nikkei 225 index on the Composite Stock Price Index (IHSG) within the capital markets of nine ASEAN nations over the period from 2019 to 2023. A total of 45 data points were selected using purposive sampling techniques to ensure relevance and alignment with the study objectives. The data analysis was conducted utilizing multiple linear regression methods with a panel data approach, processed through Eviews 12 software. The analytical procedures encompassed a comprehensive range of tests, including descriptive statistical analysis, panel regression estimation, hypothesis testing, and classical assumption diagnostics such as normality, multicollinearity, and heteroscedasticity assessments. The findings from the t-test indicate that both inflation and interest rate variables do not exert a statistically significant influence on the IHSG, whereas the Nikkei 225 index demonstrates a significant and positive effect. Moreover, the results of the F-test reveal that, when evaluated collectively, the three independent variables significantly affect the IHSG across the observed ASEAN countries.